An Examination of Bacterial Contamination of Models Used in Anatomy Laboratories - Kosif, Rengin; Avcioglu, Fatma (Interdisciplinary Perspectives on Infectious Diseases, 2018)
Background. Bacterial, viral, and parasitic transmission is a common issue involving items that are used in crowded places and are touched. In this study, it was aimed to identify the types of bacteria on models used in anatomy laboratories and the types of bacteria that contaminate students’ hands. Methods. Swab samples were taken from 30 models used in the laboratory and from the dominant hands of 94 students prior to and after contact with the models and were examined in the microbiology laboratory. Results. Five types of bacteria were isolated from the anatomy models: coagulase-negative staphylococcus, staphylococcus aureus, bacillus spp., enterococcus spp., and escherichia coli. Coagulase-negative staphylococcus, staphylococcus aureus, and bacillus spp. were isolated from the hands of the students before the contact, and additionally, enterococcus spp. were isolated after the contact. The hands were not found to be contaminated with escherichia coli originating from the models, whereas enterococcus spp. were found to be transmitted to the hands after the contact. Conclusion. The necessity of washing hands before and after working on the models and the necessity of occasionally disinfecting the models have emerged.